National survey of variations in practice in the prevention of surgical site infections in adult cardiac surgery, United Kingdom and Republic of Ireland. Issue 4 (December 2020) - ,; Aktuerk, D.; Ali, J.M.; Badran, A.; Balmforth, D.; Bleetman, D.; Brown, C.S.; Suelo-Calanao, R.; Cartwright, J.; Casey, L.; Chiwera, L.; Fudulu, D.; et al.
Summary: Background: Currently no national standards exist for the prevention of surgical site infection (SSI) in cardiac surgery. SSI rates range from 1% to 8% between centres. Aim: The aim of this study was to explore and characterize variation in approaches to SSI prevention in the UK and the Republic of Ireland (ROI). Methods: Cardiac surgery centres were surveyed using electronic web-based questionnaires to identify variation in SSI prevention at the level of both institution and consultant teams. Surveys were developed and undertaken through collaboration between the Cardiothoracic Interdisciplinary Research Network (CIRN), Public Health England (PHE) and the National Cardiac Benchmarking Collaborative (NCBC) to encompass routine pre-, intra- and postoperative practice. Findings: Nineteen of 38 centres who were approached provided data and included responses from 139 consultant teams. There was no missing data from those centres that responded. The results demonstrated substantial variation in over 40 aspects of SSI prevention. These included variation in SSI surveillance, reporting of SSI infection rates to external bodies, utilization of SSI risk prediction tools, and the use of interventions such as sternal support devices and gentamicin impregnated sponges. Conclusion: Measured variation in SSI prevention in cardiac centres across the UK and ROI is evidence of clinical uncertainty as to best practice, and has identified areas for quality improvement as well as knowledge gaps to be addressed by future research.